2018
DOI: 10.1109/tmech.2018.2801787
|View full text |Cite
|
Sign up to set email alerts
|

MR Safe Robotic Manipulator for MRI-Guided Intracardiac Catheterization

Abstract: Abstract-This article introduces a robotic manipulator to realize robot-assisted intra-cardiac catheterization in magnetic resonance imaging (MRI) environment. MRI can offer highresolution images to visualize soft tissue features such as scars or edema. We hypothesize that robotic catheterization, combined with the enhanced monitoring of lesions creation using MRI intraoperatively, will significantly improve the procedural safety, accuracy and effectiveness. This is designed particularly for cardiac electrophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(40 citation statements)
references
References 27 publications
0
40
0
Order By: Relevance
“…Modifications can be made to extend our system to multiple DoF, such as remotely controlling the frame in X and Y using the same hydrostatic actuators. Recent studies have demonstrated the feasibility of multiple DoF prototypes using hydrostatic actuation; the extension of our system to multiple DoF will be a topic for further investigation. Another limitation is that in our study we only had two operators and n = 24 experiments during motion for each targeting method.…”
Section: Discussionmentioning
confidence: 99%
“…Modifications can be made to extend our system to multiple DoF, such as remotely controlling the frame in X and Y using the same hydrostatic actuators. Recent studies have demonstrated the feasibility of multiple DoF prototypes using hydrostatic actuation; the extension of our system to multiple DoF will be a topic for further investigation. Another limitation is that in our study we only had two operators and n = 24 experiments during motion for each targeting method.…”
Section: Discussionmentioning
confidence: 99%
“…An example of this is under magnetic resonance imaging (MRI), where the strong magnetic field involved disallows any traditional robots. Towards MRI-guided robotic interventions [38], the integration of the proposed online learning algorithm and a soft robotic manipulator could enable safe and adaptive navigation in surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, image sampling methods must be selected on the basis of several aspects, such as the size, morphology, distribution of specimens, imaging resolution, sampling speed and accessibility of the adopted instruments as well as their integration capability with other manipulation tools. For example, computer tomography (CT) and magnetic resonance imaging (MRI) are widely used in the visualization of bones, tissues, and organs, but they are unsuitable for imaging small-scaled specimens, such as cells and organelles [40,41].…”
Section: Image Sampling Methodsmentioning
confidence: 99%